Letter - Chester, George
030-0102-001 National Union of Boot & Shoe Operatives Affiliated to the English, Irish & Scottish Trades Union Congresses & National Labour Party. Approved under the National Health Insurance Acts Approval No 281 and the Unemployment Insurance Acts Code No 245 28, Bedford Square London, W.C.1 General President W.R. Townley. J.P. General Secretary Geo. Chester Telephone: MUSEUM 4438 Telegrams: Natunishop. Phone London GC/FL 5 August 1938. Sir W. M. Citrine, K.B.E., General Secretary, Trades Union Congress. Dear Sir Walter, re Secretary's Department WMC/HVT/FC/572 I have to thank you for your letter of yesterday's date, in which you so kindly inform me of the manner in which the boots ordered in Bristol are to be despatched. I have advised the manufacturer accordingly, and if any difficulty arises subsequently I will get in touch with you. I am hoping it will be possible for the manufacturer to despatch direct from Bristol to Rouen, after which I understand there will be no difficulty in ultimate delivery to Spain. I am very appreciative of the assistance you have given me in this matter. Faithfully yours, Geo Chester General Secretary. 292/946/30/102